Decision Support System for Human Resource Program Prioritization Using AHP–SMART - Nadia Afriza; Nanda Siti; ilham sahputra (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2026)
Human Resource (HR) programs are a crucial aspect of improving the quality of life in rural communities; however, they are often constrained by limited resources and urgent needs. Therefore, this study implements the Analytical Hierarchy Process (AHP) and Simple Multi-Attribute Rating Technique (SMART) methods within a decision support system. The AHP method is employed to determine the criteria weights based on the relative importance of various factors influencing program implementation, including cost, benefits, community participation, needs, sustainability, ease of implementation, and risk of failure. Subsequently, the SMART method is applied to rank program alternatives based on the evaluated criteria. Accuracy testing shows that the system produces results fully consistent with manual calculations, achieving an accuracy rate of 100%. Functional testing using the black-box method indicates that all system features operate properly without errors. Meanwhile, the User Acceptance Test (UAT) results demonstrate that all respondents provided positive evaluations (scores ranging from 3 to 5), with no reported dissatisfaction, indicating that the system is feasible and well accepted by users. The results reveal that the integration of AHP and SMART provides accurate program priority recommendations, with the Community Health Program (0.7150) ranked as the top priority and Food Security Training (0.6550) as the second priority. This decision support system is expected to enhance the efficiency and accuracy of human resource decision-making in Blang Pulo Village